Primary cutaneous T‐cell lymphoma presenting as mycosis fungoides with a T‐/null‐cell phenotype: report of two cases. (29th April 2015) - Bekel, L.; Chaby, G.; Lok, C.; Dadban, A.; Chatelain, D.; Ingen‐Housz‐Oro, S.; Ortonne, N.
Summary: Variations in the clinical and histological presentation of cutaneous T‐cell lymphoma (CTCL) can hamper diagnosis. We report two cases of a novel presentation of CTCL characterized by an aberrant immunophenotype with complete loss of pan T‐cell antigens including T‐cell receptor β chain and showing the clinical and histopathological appearance of erythrodermic and plaque‐stage mycosis fungoides. Abstract : What's already known about this topic? Phenotypic aberrations with loss of some surface antigens are common findings in malignant cutaneous T‐cell lymphomas. The almost complete absence of T‐cell marker expression in mycosis fungoides has never been reported previously. What does this study add? We describe two original observations of cutaneous T‐cell lymphoma characterized by an aberrant immunophenotype with loss of pan T‐cell antigens including the T‐cell receptor β chain. Lymphoma behaviour and evolution does not appear to be modified in these cases.